Norbornenyl-pendant aromatic (co)poly(ether ether ketone)s - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (Journal of macromolecular science part A- pure and applied chemistry, 2023)
4, 4'-(Bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was utilized as a step-growth monomer for the synthesis of (co)poly(ether ether ketone)s (PEEK-NBs) via nucleophilic aromatic substitution polycondensation. A homo and five PEEK-NBs were synthesized by polycondensation of 4, 4'-difluorobenzophenone with BPA-NB and various compositions of BPA-NB and bisphenol-A, respectively. H-1 NMR spectroscopy confirmed the chemical structure and composition of PEEK-NBs. Inherent viscosity and number-average molecular weight values of PEEK-NBs were in the range 0.64 to 0.78 dL g(-1) and 62,670 to 84,470 g mol(-1), respectively, indicating the formation of polymers of reasonably high molecular weight. It was easy to dissolve PEEK-NBs in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran. Tough, transparent, and flexible films of PEEK-NBs could be cast from chloroform solution. X-Ray diffraction studies indicated amorphous nature of PEEK-NBs. Glass transition temperature (T-g) values, determined by DSC analysis, of PEEK-NBs were in the range 163 to190 degrees C and T-g values increased with the increase in mol % of BPA-NB. The post-polymerization modification of a representative PEEK-NB was demonstrated using two azido compounds, namely, 4-(azidomethyl)-7-methoxy-2H-chromen-2-one and 9-(azidomethyl)anthracene, via metal-free azide-alkene 1,3-dipolar cycloaddition reaction to obtain copoly(ether ether ketone)s appended with coumarinyl and anthracenyl moieties, respectively.
Keywords: (Co)poly(ether ether ketone)s; azide-alkene click reaction; norbornenyl groups; post-polymerization modification

Aromatic (Co)polycarbonates bearing pendant norbornenyl groups: Synthesis, characterization and post-polymerization modification - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (High Performance Polymers, 2024)
A homo- and three co-polycarbonates (PC-NBs) bearing pendant norbornenyl groups were synthesized via solution polycondensation of triphosgene with 4, 4'-(bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) or various mol % compositions of BPA-NB and bisphenol-A, respectively. 1H-NMR spectroscopy confirmed the chemical structure and composition of PC-NBs. Inherent viscosity and number-average molecular weight (Mn) values of PC-NBs were in the range 0.44 - 0.64 dL g-1 and 21,800 - 34,100 g mol-1, respectively, indicating the formation of polymers of medium to reasonably high molecular weights. Tough, transparent, and flexible films of PC-NBs could be cast from chloroform solution. X-Ray diffraction studies indicated the amorphous nature of PC-NBs. Glass transition temperature (Tg) values, determined by DSC analysis, of PC-NBs were in the range 154 - 175 degrees C and Tg values increased with the increase in mol % of BPA-NB. The post-polymerization modification of a representative PC-NB was demonstrated using 3,6-diphenyl-1,2,4,5-tetrazine via tetrazine-ene reaction.
Keywords: (co)polycarbonates; norbornenyl groups; post-polymerization modification; tetrazine-ene click reaction; thermoplastics

Synthesis and characterization aromatic copolyesters bearing pendant norbornenyl groups - Talanikar, Aniket A.; Bhong, Sahil T.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (High Performance Polymers, 2026)
4, 4'-(Bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was polymerized via phase transfer catalyzed interfacial polycondensation with an equimolar mixture (50:50 mol %) of isophthaloyl chloride (IPC) and terephthaloyl chloride (TPC) to obtain aromatic copolyester bearing pendant norbornenyl groups (PES-NB). Furthermore, three different compositions of BPA-NB and bisphenol A (BPA) were polycondensed with IPC to obtain a series of copolyesters. 1H NMR spectroscopy confirmed the chemical structure and compositions of PES-NBs. Inherent viscosity and number-average molecular weight values of PES-NBs were in the range 0.82 to 1.06 dLg-1 and 63,600 to 95,300 gmol-1, respectively, indicating the formation of polymers of reasonably high molecular weights. PES-NBs readily dissolved in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran, and tough, transparent, flexible films could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of PES-NBs. Glass transition temperature (Tg) values of PES-NBs were in the range 215 to 195 degrees C and Tg values increased with the increase in mol % of BPA-NB.
Keywords: aromatic (co)polyesters; glass-transition temperature (Tg); interfacial polycondensation; norbornenyl groups